1991
DOI: 10.1007/bf02539152
|View full text |Cite
|
Sign up to set email alerts
|

Field calibration of soil-core microcosms: Ecosystem structural and functional comparisons

Abstract: Microcosms containing intact soil-cores are a potential biotechnology risk assessment tool for assessing the ecological effects of genetically engineered microorganisms before they are released to the field; however, microcosms must first be calibrated to ensure that they adequately simulate key field parameters. Soil-core microcosms were compared with the field in terms of ecological response to the introduction of a large inoculum of a rifampicin-resistant rhizobacterium,Pseudomonas sp. RC1. RC1 was inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Pseudomonas spp. were also displaced in rhizosphere communities in other studies (5,13). It was suggested that this effect is related to the potential for fast growth, which allows the organisms to respond quickly to changing conditions in the rhizosphere (13).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Pseudomonas spp. were also displaced in rhizosphere communities in other studies (5,13). It was suggested that this effect is related to the potential for fast growth, which allows the organisms to respond quickly to changing conditions in the rhizosphere (13).…”
Section: Discussionsupporting
confidence: 61%
“…In our study, we wanted to determine whether the composition of the bacterial types in rhizospheres was affected by inoculation with S. meliloti. Transiently occurring changes in microbial community structure in response to inoculation have been detected in studies performed with nonsymbiotic rhizosphere bacteria (5,13,40,41). To understand the importance of the symbiotic relationship, we included analyses of bacterial populations in the rhizospheres of a host plant, M. sativa, and a nonhost plant, the weed C. album.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of soil or seeds with pseudomonads for biocontrol purposes implies the release of cells in large numbers (often higher than the number of RCFP), which can cause a transient increase in the number of total culturable fluorescent pseudomonads (1,49) and even sometimes in that of total culturable aerobic bacteria (4,49). At 19 days after sowing, the number of total culturable fluorescent pseudomonads at the rhizoplane was not affected, but that of RCFP was reduced (Table 1), similar to the results of other studies (10,36,47).…”
Section: Resultsmentioning
confidence: 99%
“…Before microcosms can be used as a risk assessment tool they must first be calibrated with field observations to ensure a reliable extrapolation of experimental results [3]. The objective of this study was to field calibrate an aquatic microcosm.…”
Section: Introductionmentioning
confidence: 99%